Moving Particle Level-Set (MPLS) method for incompressible multiphase flow computation - Ng K.C.; Hwang Y.H.; Sheu T.W.H.; Yu C.H. (Elsevier B.V., 2023)
Mesh generation; Multiphase flow; Calibration parameters; Computational deficiency; Interpolation schemes; Level Set; Moving particle semi-implicit; Moving particle semiimplicit method; Moving particles; Particle methods; Numerical methods